Implementasi Sistem Perangkat Ukur Status Gizi Berbasis IOT: Posyandu Lansia Desa Karangan - Raihan, Muhammad; Ristian, Uray; Hasfani, Hirzen (Journal of Information System Research (JOSH), 2024)
Posyandu lansia is a government initiative designed to improve the well-being and health of older people. The program includes periodic evaluation of nutritional status, which includes measuring body weight, height and looking up the nutritional status of the elderly. The manual measurements often used in posyandu, while accurate, are often time-consuming and require high accuracy from health workers. To overcome these challenges, a nutritional status measurement device system called SIGIZI was developed. This system is connected to the measuring device using the HTTP protocol to allow direct data communication between the measuring device and the website in real-time. The system uses load cell sensors to measure weight and ultrasonic sensors for height. Data from the sensors is sent to the server in real-time via HTTP protocol, using stable connections from various providers. After the data is received, the system automatically calculates the Body Mass Index (BMI) by dividing body weight by the square of height, the results of this calculation are used to assess the nutritional status of the elderly. Analysis reveals that the BMI values obtained from SIGIZI and manual measurements differ by an average of 0.4 kg/m², with an error rate of 1.7% and an accuracy of 98.3%, indicating that SIGIZI's measurements are very close to those obtained manually. Furthermore, the HTTP protocol used for SIGIZI data transmission shows a stable connection with Axis (3.0 ms), Telkomsel (3.2 ms), and Tri (3.6 ms). Additionally, the average data transmission delay of 203 ms falls within the acceptable range according to the TIPHON standard, demonstrating that the system is reliable for efficient data transmission.